Launching a Business - Barringer, Bruce (Business Expert Press, 2013)
Ebook from IG Library ; If you're thinking of opening up your own business, you'll need this book. This is a hands-on book that focuses on the tasks that you or any new business owner must complete in the first 100 days of launching a business. Think of it this way: Imagine you've conceived a business idea, written a business plan, raised seed capital, and are set to launch your business on October 1. Now, what would you actually do on October 1, October 2, October 3, and so forth? How would you set your priorities? How would you know which tasks are the most urgent? Although the answers to these questions vary depending on the business, there are a set of key activities that all businesses must accomplish to get their businesses off to a good (and legally proper) start. This book provides examples that include securing proper business licenses and permits; setting up a bookkeeping system; negotiating a lease; buying insurance; entering into contracts with vendors; recruiting and hiring employees; and making the first sale. Broader issues such as developing a business model and building a brand will also be touched upon, but the primary focus of this book is getting you focused on the practical issues that you'll need, as a new business owner, to accomplish, and accomplish correctly, and to get your business off to a good start. To help you prioritize and track the activities that must be completed at the onset of a business, this book will teach you how to set up a 'First 100 Days Plan,' with the template (titled First 100 Days Plan) included in this book.